Cinética, equilíbrio e termodinâmica do processo de adsorção de íons metálicos utilizando resíduos da indústria de mandioca como biossorventes - Schwantes, Daniel (2013)
The present work aimed evaluate the use of solid wastes from the industry of cassava root processing (Manihot esculenta Crantz) (bark, bagasse and the mix bark + bagasse), as natural adsorbents for the removal of the metal ions Cd+2, Pb+2 and Cr3+ from polluted hydric bodies. In the first moment, the biosorbents were characterized chemically, structurally and morphologically. After this step, adsorption tests were conducted aiming to determine the ideal conditions of pH, mass of adsorbent and contact time between the adsorbent/adsorbate for the removal process of these metal ions. The adsorption kinetics was evaluated by the mathematical models of pseudo-first order, pseudo-second order, Elovich and intraparticle diffusion. By this primary results were obtained the isotherms of adsorption, which were linearized by the mathematical models of Langmuir, Freundlich and Dubinin-Radushkevich. Besides, were also evaluated the effect of temperature and the biosorbents desorption capacity. By the micrographs was observed surfaces with characteristics favorable to adsorption process, and by the infrared spectrum were identified possible structural compounds like lignin, cellulose and hemicellulose. The pHPCZ determinated was 6.00, 6.17 and 6.24 for the biosorbents bark, bagasse and bark + bagasse, respectively. The mass tests demonstrate that the proportion biosorbent/contaminant of 8 g/L is enough for an efficient removal of the metal ions. The influence of pH in the adsorption was determinated in the range of pH (4.0 to 6.0) for Cd2+, Pb2+ and Cr3+, being the more adequate range between the pH 5.0 and 6.0, so it was chosen to work with the pH of 5.5. The time for the dynamic equilibrium for the adsorption process is 60 min for the three materials, for the three studied metal ions. The kinetics model of pseudo-second order had the best fitting to the experimental data. The cassava adsorbents have proved to be efficient in the adsorption of the metallic ions Cd2+, Pb2+ and Cr3+, being the adsorption process of endothermic character, i. e., influenced by the increase of temperature. The cassava materials presented good desorption of Cd2+ and Pb2+, being only the metal Cr3+ the one who presented very low desorption rates, for the biosorbents and for the activated carbon, indicating that this metal is strongly ligated to the adsorbent sites. By the obtained results it can be concluded that the use of the wastes bark, bagasse and bark + bagasse of cassava presented themselves as potential biosorbents viable for the decontamination of hydric bodies polluted by metallic ions Cd2+, Pb2+ e Cr3+. In this way, it is verified that this practice complements the final steps of the productive chain of cassava, bringing a brand new destiny for these solid wastes from the cassava agroindustry